Are wearable photoplethysmogram-based heart rate variability measures equivalent to electrocardiogram? A simulation study - Dewig, H. G.; Cohen, J. N.; Renaghan, E. J.; Leary, M. E.; Leary, B. K.; Au, J. S.; Tenan, M. S. (Sports Medicine, 2024)
Key Points